Regression of cardiomyocyte hypertrophy in SHR following chronic inhibition of the Na+/H+ exchanger - Camilión de Hurtado, María Cristina (2002)
Objective: Experiments were performed to examine the effect of chronic inhibition of the Na+/H+ exchanger isoform-1 (NHE-1) on cardiac hypertrophy of spontaneously hypertensive rats (SHR). Methods: SHR were orally treated during 1 month with two different doses (0.3 and 3.0 mg/kg/day) of the NHE-1 inhibitor, cariporide, or nifedipine (10.0 mg/kg/day). Results: The two doses of cariporide did not differ in their effects after 1 month of treatment, since both induced a slight decrease in systolic blood pressure (SBP) of ∼6 mmHg and regression of the heart weight to body weight ratio (mg/g) from 3.28±0.05 to 3.04±0.05 (0.3 mg) and 2.99±0.10 (3.0 mg, P<0.05). Nifedipine, given for the same period, produced similar reduction in the hypertrophy index (3.03±0.05), but with a much greater decrease in arterial pressure (35.6±7.4 mmHg). Chronic treatment with cariporide induced a complete regression of the augmented cross sectional area of left ventricular myocytes without significant changes in collagen content, serum procollagen 1 propeptide levels or myocardial distensibility. Conclusions: NHE inhibition represents a novel approach to induce regression of pathological hypertrophy of the heart. The finding can be rationalized mechanistically by previous in vitro studies suggesting a role of the NHE in the development of myocardial hypertrophy.